Rancang Bangun Sistem Presensi Biometrik Sidik Jari Berbasis IoT dengan Arduino Node MCU - Kusuma, Rizky Tri; Solikhun, Solikhun; Saputra, Widodo; Windarto, Agus Perdana; Nasution, Della Fatricia (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
Presence is a procedure or process that needs to be carried out by all employees or members of a company or agency. The attendance register is a reference and benchmark for assessing, measuring, and determining the quality and quantity of each member or employee of the company or agency. Presentations carried out manually are considered less effective and efficient in terms of time and usage. So it is necessary to build an intelligent attendance system, one of which is by creating an intelligent attendance system that uses IoT-based fingerprint recognition technology with an Arduino controller and outputs to an Internet or intranet server. Based on the results obtained in the research, administrators can float their side servers freely. The time for sending data from the presence device to the server uses the POST method, with an average time of 8 seconds on an intranet network with a maximum distance of 25 meters from the wireless router or access point. By creating this attendance system, it makes it easier for the Surya Pematangsiantar Education Foundation to record the attendance of teachers and staff, especially SMK units.